POPULATION GROWTH AND LAND USE CHANGE IN BENUE STATE: IMPLICATION FOR SOCIAL SECURITY AND ECONOMIC DEVELOPMENT IN SANKERA (2001 – 2023) - Asaasuen, Terngu; Ereh Oko, Peter; Orya Amande, Nelson; Terseer Hundu, Williams (African Journal of Social and Behavioural Sciences, 2024)
The Earth’s environment has become progressively configured by multiple land use and land cover changes, which are all products of global intensification in anthropogenic activities relative to sustained population growth over space and time. This paper uses a frequency distribution table, simple percentages, t-test, correlation statistics, geographic information system (GIS) and remote sensing as techniques for data analysis to examine the phenomenon of population growth against the background of land use and land cover changes in the Sankera Geographical District of Benue State. These variables are examined in relation to their implications for social security and economic development. Primary data were obtained through the administration of 180 questionnaires via multi-stage sampling, field surveys and photo elicitation as well as key informant’s interview (KIIs). The secondary data were sourced from journal articles with related focuses. The study revealed that there has been significant growth in the size of the population in the study area from 2001-2023, which is a combined function of excess fertility over mortality as well as migration. Similarly, the results of this study show that population growth in the study area has significantly impacted land use and cover changes, with adverse effects on social security and economic development. The paper accordingly recommends that effective family planning measures be made available for intending users, the adoption of more effective land use policies, agricultural mechanization and the pursuit of greater security to protect the vulnerable population in the locality.